Portable Lightboard Use in Online Higher Education - Nuray Gedik; Esra Pınar Uça Güneş; Ayfer Beylik; Alper Çabuk; Engin Tıraş (Open Praxis)
The emergency distance education period has led to new instructional experiences and unique practices in higher education. This study focuses on one such practice that included portable lightboards designed as a cost-effective solution to support instructors’ online teaching processes from their homes. Using a case study design, data were collected via using through interviews with eight students and nine instructors who used the lightboard for the first time in order to to explore their perceptions and lived experiences. The findings obtained in this study showed that the instructors could benefit from the writing/drawing feature supported by the dynamic drawing principle of multimedia learning from their homes. Student engagement was enhanced due to offering a sustainable learning environment resembling face-to-face courses with unique limitations. The results offer key aspects of portable lightboards with great potential for future online or blended learning environments.